Severe T-System Remodeling in Pediatric Viral Myocarditis - Fiegle, Dominik J.; Schöber, Martin; Dittrich, Sven; Cesnjevar, Robert; Klingel, Karin; Volk, Tilmann; Alkassar, Muhannad; Seidel, Thomas (Frontiers in Cardiovascular Medicine, 2021)
Chronic heart failure (HF) in adults causes remodeling of the cardiomyocyte transverse tubular system (t-system), which contributes to disease progression by impairing excitation-contraction (EC) coupling. However, it is unknown if t-system remodeling occurs in pediatric heart failure. This study investigated the t-system in pediatric viral myocarditis. The t-system and integrity of EC coupling junctions (co-localization of L-type Ca2+ channels with ryanodine receptors and junctophilin-2) were analyzed by 3D confocal microscopy in left-ventricular (LV) samples from 5 children with myocarditis (age 14 ± 3 months), undergoing ventricular assist device (VAD) implantation, and 5 children with atrioventricular septum defect (AVSD, age 17 ± 3 months), undergoing corrective surgery. LV ejection fraction (EF) was 58.4 ± 2.3% in AVSD and 12.2 ± 2.4% in acute myocarditis. Cardiomyocytes from myocarditis samples showed increased t-tubule distance (1.27 ± 0.05 μm, n = 34 cells) and dilation of t-tubules (volume-length ratio: 0.64 ± 0.02 μm2) when compared with AVSD (0.90 ± 0.02 μm, p < 0.001; 0.52 ± 0.02 μm2, n = 61, p < 0.01). Intriguingly, 4 out of 5 myocarditis samples exhibited sheet-like t-tubules (t-sheets), a characteristic feature of adult chronic heart failure. The fraction of extracellular matrix was slightly higher in myocarditis (26.6 ± 1.4%) than in AVSD samples (24.4 ± 0.8%, p < 0.05). In one case of myocarditis, a second biopsy was taken and analyzed at VAD explantation after extensive cardiac recovery (EF from 7 to 56%) and clinical remission. When compared with pre-VAD, t-tubule distance and density were unchanged, as well as volume-length ratio (0.67 ± 0.04 μm2 vs. 0.72 ± 0.05 μm2, p = 0.5), reflecting extant t-sheets. However, junctophilin-2 cluster density was considerably higher (0.12 ± 0.02 μm−3 vs. 0.05 ± 0.01 μm−3, n = 9/10, p < 0.001), approaching values of AVSD (0.13 ± 0.05 μm−3, n = 56), and the measure of intact EC coupling junctions showed a distinct increase (20.2 ± 5.0% vs. 6.8 ± 2.2%, p < 0.001). Severe t-system loss and remodeling to t-sheets can occur in acute HF in young children, resembling the structural changes of chronically failing adult hearts. T-system remodeling might contribute to cardiac dysfunction in viral myocarditis. Although t-system recovery remains elusive, recovery of EC coupling junctions may be possible and deserves further investigation.